How Different Forms of Social Capital Created Through Project Team Assignments Influence Employee Adoption of Sustainability Practices - Reddy, Sheila M. W.; Torphy, Kaitlin; Liu, Yuqing; Chen, Tingqiao; Masuda, Yuta J.; Fisher, Jonathan R. B.; Galey, Sarah; Burford, Kyle; Frank, Kenneth A.; Montambault, Jensen R. (Organization & environment, 2021)
Can social capital created through project assignments increase the diffusion of sustainability practices, and if so, what types of social ties and conditions are likely to be most effective in doing so? We use a mixture of survey and qualitative evidence from a social network at a large organization, The Nature Conservancy, to help answer these questions. Our analysis supports the argument that cross-organizational unit ties promote adoption of complex practices by having the benefits of both external and internal ties (i.e., exposure to novel practices and on-the-job social learning experiences, respectively). Specifically, staff learned new sustainability practices from project teammates in other organizational units who were already employing sustainability evidence-based practices. Thus, a practical and cost-effective way to promote organizational learning for sustainability may be to strategically form cross-organizational unit project teams that include sustainability practice innovators. Internal fellowships and short-term assignments may be other effective ways to do this.